RELIGIOUS PLURALITY AT PUJA MANDALA NUSA DUA BALI BUALU TRADITIONAL VILLAGE, BENOA URBAN VILLAGE, SOUTH KUTA DISTRICT - Mancapara, I Gede Pasek; I Nengah Duija; Ni Ketut Srie Kusuma Wardhani (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
This research examines the religious plurality that occurs at Puja Mandala Nusa Dua Bali with a problem formulation; (1) Why does the practice of religious plurality emerge in Puja Mandala Nusa Dua Bali, (2) What is the process of religious plurality in Puja Mandala Nusa Dua Bali, (3) What are the implications of religious plurality in Puja Mandala Nusa Dua Bali. The theories used are Weber's social action theory, Bourdieu's social practice theory, Blau's exchange theory, and Parson's structural functionalism theory. This type of qualitative research uses a phenomenological approach. The research results show that the emergence of religious plurality in Puja Mandala is due to; (1) Historical Factors of Religious Harmony in Bali, (2) Factors of creative actors, (3) Motive and Goal Factor, (4) Imaginary Idea of Harmony Factor. The practice of religious plurality that occurs at Puja Mandala includes; (1) there is online or interpersonal social interaction, 2) there is PAUB/ Inter-Religious Association, (3) there is intrinsic and extrinsic social exchange (4) there are values used in individual and group activities. The implications of religious plurality in Puja Mandala Nusa Dua Bali are in the form of; (1) adaptation, (2) integration, (3) achieving goals, (4) maintaining unity motivation. The findings in this research are the existence of superstructure, infrastructure and structures, which because the realization of religious plurality at Puja Mandala